Multicyclic indentation on brittle glasses. Issue 18 (15th September 2021) - Bentoumi, M.; Raouache, E.H.; Driss, Z.; Montagne, A.; Iost, A.; Mejias, A.; Chicot, D.
Abstract: Instrumented indentation testing is widely used to determine the mechanical properties of materials. In particular, this technique allows to study brittle materials for which cracks can be generated around the impression during the indentation test. Cracking can result in the formation of pop-ins on the curve load-segment which can be used to characterize the cracking resistance of the material. In this work, the mechanical properties of the studied materials were determined by applying multicyclic indentation tests. The pop-in phenomenon is mainly observed under constant multicyclic loading on Zerodur® glass whereas under progressive multicyclic loading, this phenomenon appears for all glasses after several indentation cycles. The indentation fracture toughness, (KIc ), was calculated from the developed cracks' length by using different established relationships. Finally, the values of (KIc ) and brittleness factor are compared with each other, allowing a classification of the tested glasses according to their resistance to cracking.